1990
DOI: 10.1002/art.1780330418
|View full text |Cite
|
Sign up to set email alerts
|

Sequence of i‐e genes from autoimmune new zealand white mice

Abstract: Autoimmune New Zealand white (NZW) mice contribute to (New Zealand black × New Zealand white)F1 mice 1 or more major histocompatibility complex‐linked genes that strongly correlate with susceptibility to murine lupus. The NZW class II major histocompatibility complex genes, I‐Eα and I‐Eβ, were cloned and sequenced and found to differ from normal B10.PL (H‐2u) mice by 3 amino acids in the first domain of the I‐Eβ subunit. Of these differences, the arginine at position 72 of NZW mice could be an important diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

1991
1991
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 18 publications
0
2
1
Order By: Relevance
“…the New Zealand model of lupus (13,14,38,39). Our results, however, indicate that lupus-like disease in this model is not influenced by Ea z and/or Eb z genes.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…the New Zealand model of lupus (13,14,38,39). Our results, however, indicate that lupus-like disease in this model is not influenced by Ea z and/or Eb z genes.…”
Section: Discussioncontrasting
confidence: 51%
“…The present studies were designed to determine whether Ea z and/or Eb z genes account for the genetic contribution of H2 z to lupus-like disease in New Zealand hybrid mice. Previous studies have shown that the ␤1 exon sequences of these genes are identical with those reported for Ea u and Eb u genes (14,(37)(38)(39)(40)(41). Based on various sequence homologies, it was predicted that these class II molecules would enhance the production of pathogenic IgG autoantibodies in FIGURE 3.…”
Section: Discussionmentioning
confidence: 71%
“…Heterozygosity at Lbw1 (H‐2 d/z ) conferred the greatest susceptibility than either H‐2 d or H‐2 z haplotypes consistent with previous studies (10, 11). NZB (H‐2 d ) and NZW (H‐2 z ) class II genes (12–16), the NZW TNF‐α gene (9, 17), or both (8) have been suggested as candidates for this locus. Recently, a recessively transmitted NZW locus, designated Sles1 , that also mapped to the MHC region was suggested to act as an epistatic modifier that suppressed autoimmune disease in the NZW strain (18).…”
Section: Nz Susceptibility Locimentioning
confidence: 99%